1994
DOI: 10.1029/93jd02598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biomass burning on summertime nonmethane hydrocarbon concentrations in the Canadian wetlands

Abstract: Approximately 900 whole air samples were collected and assayed for selected C2‐C10 hydrocarbons and seven halocarbons during the 5‐week Arctic Boundary Layer Expedition (ABLE) 3B conducted in eastern Canadian wetland areas. In more than half of the 46 vertical profiles flown, enhanced nonmethane hydrocarbon (NMHC) concentrations attributable to plumes from Canadian forest fires were observed. Urban plumes, also enhanced in many NMHCs, were separately identified by their high correlation with elevated levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 70 publications
6
76
0
Order By: Relevance
“…Using the same WAS data set, but with different plume selection and averaging, Simpson et al (2011) reported an ethane to CO ER for Canadian BB during ARC-TAS of 4.6 ± 0.9 pptv ppbv −1 , consistent with the mean ethane NEMR determined in this work. Simpson and co-authors also reported an ethane to CO ER from a Siberian boreal forest fire plume interception on 29 June (4.63 ± 0.08 pptv ppbv −1 , corresponding to plume 19 in this work: 4.5 ± 0.5 pptv ppbv −1 ), which combined with findings from a previous study (ABLE-3B, Blake et al, 1994) led the authors to conclude that there may be a characteristic boreal forest fire emission signature. However, our plume 7 was also traced to the Siberian boreal forest region and has an ethane to CO NEMR of 15 ± 2 pptv ppbv −1 .…”
Section: Alkanessupporting
confidence: 71%
“…Using the same WAS data set, but with different plume selection and averaging, Simpson et al (2011) reported an ethane to CO ER for Canadian BB during ARC-TAS of 4.6 ± 0.9 pptv ppbv −1 , consistent with the mean ethane NEMR determined in this work. Simpson and co-authors also reported an ethane to CO ER from a Siberian boreal forest fire plume interception on 29 June (4.63 ± 0.08 pptv ppbv −1 , corresponding to plume 19 in this work: 4.5 ± 0.5 pptv ppbv −1 ), which combined with findings from a previous study (ABLE-3B, Blake et al, 1994) led the authors to conclude that there may be a characteristic boreal forest fire emission signature. However, our plume 7 was also traced to the Siberian boreal forest region and has an ethane to CO NEMR of 15 ± 2 pptv ppbv −1 .…”
Section: Alkanessupporting
confidence: 71%
“…Sample canisters were evacuated to 10-2 torr and shipped to the site for sample collection. Although most canisters have shown reliability and stability in the containment of various halocarbons and hydrocarbons, some have also displayed growth of light olefins with time [Blake et al, 1994]. Ambient air rebaking of these canisters has helped to resolve the olefin growth problem.…”
Section: Uc Irvinementioning
confidence: 99%
“…All canisters used in this study were pre-cleaned and evacuated by the Rowland-Blake group at the University of California, Irvine (UCI). Detailed information of the preparation and pre-conditioning of the canisters can be found elsewhere (Blake et al, 1994;Simpson et al, 2010). After sampling, canisters with air samples were sent back to the laboratory at UCI for VOC analysis by a GC-MSD/FID/ECD system within 1 week of collecting the canister samples.…”
Section: Offline Gc-msd/fid/ecdmentioning
confidence: 99%